Pengembangan Modul Elektrokimia dengan Pendekatan Kontekstual Chemoentrepreneurship untuk SMA - Bayu Bramasta Giri; Suhadi Ibnu; Sutrisno Sutrisno (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this research is to produce an electrochemical contextual chemoentrepreneurship module that is validated according to the criteria of BSNP materials eligibility, namely content eligibility, linguistic feasibility, presentation feasibility, and the feasibility of the graft and knowing Effectiveness of student learning outcomes. The development model adopted the Model 4-D with the stages of defining, designing, developing, and desimination. Data on the feasibility of teaching materials is obtained from content and material validation, individual test, field test is limited while the effectiveness data is obtained from the difference learning outcomes between the experimental and the control group. The validation and test results are obtained as follows (1) the average value of the content expert validator and learning material is very decent criteria, (2) individual trials with excellent criteria, and (3) limited field trials is Very good criteria. The development module is well-deserved to be used as a learning resource and effectively improve student learning outcomes. Abstrak: Penelitian ini bertujuan menghasilkan modul elektrokimia kontekstual Chemoentrepreneurship tervalidasi sesuai kriteria kelayakan bahan ajar BSNP, yakni isi, kebahasaan, penyajian, dan kegrafisan serta mengukur efektivitas modul terhadap hasil belajar. Model pengembangan mengikuti model 4-D dengan tahapan pendefinisian, perancangan, pengembangan, dan desiminasi. Data kelayakan modul diperoleh dari validasi isi dan materi, uji perorangan, uji lapangan terbatas sedangkan data efektivitas diperoleh dari perbedaan hasil belajar antara kelompok eksperimen dengan kelompok kontrol. Hasil penelitian (1) nilai validasi isi dan materi pembelajaran memiliki kriteria sangat layak, (2) uji coba perorangan kriteria sangat baik, dan (3) uji coba lapangan kriteria sangat baik. Modul efektif digunakan dalam pembelajaran hal ini ditunjukkan oleh ketuntasan hasil belajar peserta didik kelompok eksperimen lebih tinggi daripada kelompok kontrol.